Pengaruh Kedisiplinan Terhadap Peningkatan Produktivitas Kerja PT. Buluh Cawang Plantations Kabupaten Ogan Komering Ilir (OKI) - Fatimah, Isnaini; Zunaidah; Dameria, Lina; Farla, Wita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of Discipline on increasing employee work productivity at PT. Buluh Cawang Plantations, Ogan Komering Ilir (OKI) Regency. The population in this study are employees of PT. Buluh Cawang Plantations section of harvest production using simple random sampling, totaling 58 respondents. Data collection method used in this study using a questionnaire. The analysis technique used is simple linear regression analysis. The data in this analysis is processed using the Statistical for Product and Service Solution (SPSS) program. Based on the analysis of this study shows that Discipline has a positive and significant effect on increasing employee work productivity at PT. Buluh Cawang Plantations, Ogan Komering Ilir (OKI) Regency.